ESTABLISHMENT OF QANUN GAMPONG DURIAN KAWAN, SELATAN ACEH: ACCORDANCE OF PRINCIPLES AND PROCEDURE DIFFERENCES: PEMBENTUKAN QANUN GAMPONG DURIAN KAWAN, ACEH SELATAN: KESESUAIAN ASAS DAN PENYIMPANGAN PROSEDUR - Musdalizar Musdalizar; Zahlul Pasha Karim; Sitti Mawar (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2022)
Qanun Gampong Durian Kawan, South Aceh Regency Number: 05 of 2018 concerning Management and Utilization of Natural Resources (Forest and Water Maintenance Customs) is one of the reusam codification efforts which usually regulates people’s behavior regarding habits carried out by the community in an unwritten form. However, what should be suspected is whether the gampong qanun has gone through the applicable legislative process. The main problem in this study is how the process of forming the Qanun Gampong Durian Kawan is and how the suitability of the process of forming the Qanun is reviewed with the South Aceh Regent Regulation Number 77 of 2017. The methodology in this research uses a qualitative research type with a descriptive approach. The results show that the process of forming Qanun Gampong Durian Kawan, South Aceh Regency Number: 05 of 2018 concerning Management and Utilization of Natural Resources (Forest and Water Maintenance Customs) through 4 stages, namely first, pre-design phase by collecting community aspirations, second, design phase through deliberation with various levels of society, third, the stipulation phase, namely ratifying the qanun based on the results of deliberation decisions and fourth, the promulgation phase, namely signing by the keuchik. Judging by the guidelines for the formation of gampong legal products in South Aceh, in principle, they are appropriate because they use the principle of deliberation, but from a systematic and technical perspective there are still many that are not in accordance with South Aceh Regent Regulation Number 77 of 2017.